The Impact of Covid-19 Pandemic on the Financial Performance of Islamic Banks in the Philippines - Najeeb Razul A. Sali (International Journal on Economics, Finance and Sustainable Development, 2022)
This paper investigated the impact of the Covid-19 Pandemic on the performance of Islamic banks in the Philippines. It used the quarterly data before and during the pandemic. To empirically measure its impact on the Islamic bank in the country, this study used significant different tests to ascertain differences in the financial performance of the bank starting from the 1st quarter to the 4th quarter of 2019 used as a proxy for pre-pandemic variable and the 1st to 4th quarter of 2020 which was during the heights of the pandemic as data that represents the duration of the crisis. The result shows that the overall bank size during the pandemic was reduced by 2.08% while changes in return on deposits and return on equity before and during the pandemic were not statistically significant. However, there was enough evidence to show that Islamic deposits, return on assets, and net income, were significantly positively affected by the Covid-19 Pandemic. Test for significant difference further ascertained that the decrease in capital adequacy ratio during the pandemic was found statistically significant. It suggested that Islamic banking in the Philippines fared differently compared to its conventional counterparts in the country.